Knockout of Formyl Peptide Receptor-1 Attenuates Cigarette Smoke–Induced Airway Inflammation in Mice - Gao, Lijuan; Zeng, Ni; Yuan, Zhicheng; Wang, Tao; Chen, Lei; Yang, Deqing; Xu, Dan; Wan, Chun; Wen, Fuqiang; Shen, Yongchun (Frontiers in Pharmacology, 2021)
Objective The formyl peptide receptor-1 (FPR-1) has been reported to be implicated in the regulation of inflammatory disorders, while its role in cigarette smoke (CS)-induced airway inflammation has not been fully explained. In this study, we investigated the role of FPR-1 in CS-induced airway inflammation and possible mechanism through gene knockout (KO) technology and transcriptional study. Methods FPR-1 KO or wild type C57BL/6 mice were exposed to mainstream CS to establish airway inflammation model. Cell counts and proinflammatory cytokines were measured in bronchoalveolar lavage fluid (BALF). Lung tissues were collected for histological examination, polymerase chain reaction, Western Blot, transcriptomic gene study, and related bioinformatics analysis. Results CS exposure induced significant histological inflammatory changes, increased neutrophils and proinflammatory cytokines in the BALF of wild-type mice, which were all attenuated by KO of FPR-1. Transcriptomic gene study showed a total of 198 upregulated genes and 282 downregulated genes in mouse lungs. Bioinformatics analysis including Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) suggested these differentiated expressed genes were significantly related to the immune, chemotaxis responses, and cross-talked with a complicated network of signaling pathways including NF-κB. Western Blot validated that KO of FPR-1 inhibited CS induced NF-κB activation. Conclusions Knockout of FPR-1 significantly ameliorates CS-induced airway inflammation in mice, which possibly via its related immune-chemotaxis responses and inhibition of NF-κB activation.